Cold autoantibody interference in pretransfusion testing and its resolution: a case report - Yousuf, Rabeya; Raghvan, Hari Priya; Suhemi, Nur Afifah; Abdullah Thalith, Nor Fadzliana; Tang, Yee Loong; Aziz, Suria Abdul (Bangladesh Journal of Medical Science, 2024)
We report a case of cold autoantibody detected in a 69-year-old gentleman diagnosed with chronic lymphocytic leukemia and cold autoimmune hemolytic anaemia. Pretransfusion testing showed panagglutination in ABO grouping, antibody screening and identification, with positive direct antiglobulin test (DAT) and positive control cells. A cold autoantibody was suspected, however, the test using a prewarm method and washed RBC with warm saline failed to resolve it. Further tests using DTT-treated cells resolved the grouping as AB RhD positive and DAT as positive with anti-C3d only (control negative). Cold autoadsorption was done and repeated antibody screening using cold-autoadsorped plasma was negative, excluding the presence of alloantibody. The cold-agglutinin titer was >1028 having a wide thermal range. Crossmatching using cold autoadsorped plasma with the AB-positive donor blood was compatible and the patient was transfused safely. For such cold autoantibody cases, an extensive immunohematological workup is required to exclude underlying alloantibody for transfusion safety and efficacy. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1238-1242